Discursive Communities, Protest, Xenophobia, and Looting in South Africa: A Social Network Analysis. Issue 1 (2nd January 2022) - Mathe, Limukani; Motsaathebe, Gilbert
Abstract: The article informs on a study that employed a digital ethnographic approach to analyse a network of human relationships and connections based on the physical and social phenomena of political protest and xenophobia, accompanied by looting and the destruction of property in South Africa. It examines how social media have been used to fuel violence, protest, xenophobic attacks, and the looting of shops, and for ordinary citizens to post videos or images of protest actions on the internet. This article uses the tenets of propaganda (the propaganda model) as a social media theory to analyse online activism in various forms, such as journalism and political protest for citizen mobilisation and participation. The article finds that participation in groups (reflected by hashtags) is determined by shared interests or grievances (mob psychology) and shaped by propaganda. It concludes that social media are tools or platforms that can be used for good or bad, echoing realities on the ground, such as poverty and social inequalities, as causes of political protest, xenophobia, and looting in South Africa. Political players and activists drive their own agendas by exploiting or emphasising the causes of poverty and social inequalities, thereby attracting followers who reaffirm their messages by tweeting and retweeting. The article concludes that social media are weaponised for protest, causing panic, anxiety, and discomfort that linger for an unspecified period until another outbreak.